Speaking Q'anjobal, Spanish, and English: a world where other worlds are possible. Issue 3 (3rd July 2019) - Guerrero-Arias, Beatriz Eugenia
ABSTRACT: Currently, there is a call for more humane ways in humanities, for transitions to a world where other worlds are possible. This qualitative case study analyzes an emergent translingual boy's participation in diverse spatial repertoires to address issues of learning and community belonging. José is a 4-year-old preschool Guatemalan-ancestry boy, who speaks Q'anjob'al, Spanish, and English. He was placed in an English classroom with daily 30-min Spanish and English pullout. José participated in the pullout to a desirable extent but was marginalized in the English classroom. At home, José had varied opportunities for participating in diverse spatial repertoires. I discuss how home and school have different conceptions of learning and community belonging, and how the home setting with pluriversed spatial repertoires sheds light on a pedagogical practice aimed at transitioning towards a world where other worlds are possible.